A century of protests : peasant politics in Assam since 1900 - Saikia, Arupjyoti, 1969- (Routledge, Taylor & Francis Group, 2014)
Addressing an important gap in the historiography of modern Assam, this book traces the relatively unexplored but profound transformations in the agrarian landscape of late- and post-colonial Assam that were instrumental in the making of modern Assamese peasantry and rural politics. It discusses the changing relations between various sections of peasantry, state, landed gentry, and politics of different ideological hues - nationalist, communist and socialist - and shows how a primarily agrarian question concerning peasantry came to occupy the centre stage in the nationalist politics of the state. It will especially interest scholars of history, agrarian and peasant studies, sociology, and contemporary politics, as also those concerned with Northeast India. --